2020
DOI: 10.1177/0363546520969205
|View full text |Cite
|
Sign up to set email alerts
|

Foot Core Training to Prevent Running-Related Injuries: A Survival Analysis of a Single-Blind, Randomized Controlled Trial

Abstract: Background: Running-related injuries (RRIs) are a pervasive menace that can interrupt or end the participation of recreational runners in this healthy physical activity. To date, no satisfactory treatment has been developed to prevent RRIs. Purpose: To investigate the efficacy of a novel foot core strengthening protocol based on a ground-up approach to reduce the incidence of RRIs in recreational long-distance runners over the course of a 1-year follow-up. Study Design: Randomized controlled trial; Level of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 56 publications
(85 reference statements)
1
74
0
9
Order By: Relevance
“…For example, lower limb kinematics during locomotor tasks have been shown to be related to the responsiveness to exercise-based treatment in individuals with knee osteoarthritis ( Kobsar et al, 2015 ) and patellofemoral pain ( Watari et al, 2016 ). Seeing that the intervention protocol in this study was effective in reducing the incidence of running-related injuries ( Taddei et al, 2020a ), the results of this study can help understanding how individual variations of baseline motor behaviors can influence the response to these exercises and this approach can help guiding treatment strategies that are more individual-centered, taking into account their initial mechanical patterns. Future studies should investigate whether the identified movement patterns could be influencing the protective effects against running-related injuries that this exercise program has presented, by stratifying the experimental groups based on kinematic patterns.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, lower limb kinematics during locomotor tasks have been shown to be related to the responsiveness to exercise-based treatment in individuals with knee osteoarthritis ( Kobsar et al, 2015 ) and patellofemoral pain ( Watari et al, 2016 ). Seeing that the intervention protocol in this study was effective in reducing the incidence of running-related injuries ( Taddei et al, 2020a ), the results of this study can help understanding how individual variations of baseline motor behaviors can influence the response to these exercises and this approach can help guiding treatment strategies that are more individual-centered, taking into account their initial mechanical patterns. Future studies should investigate whether the identified movement patterns could be influencing the protective effects against running-related injuries that this exercise program has presented, by stratifying the experimental groups based on kinematic patterns.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, during running, wherein the motor behavior is more dynamic, the function of the FA is even more important, with evidence of its influence on running-related injury prevention. Taddei et al (2020a) showed that a foot-core exercise intervention program in middle and long-distance recreational runners resulted in 2.4 times lower injury incidence when compared to a control group in a 12 months period.…”
Section: Introductionmentioning
confidence: 98%
“…Another recently published RCT revealed that a novel foot-core muscle strengthening program was effective in prevention of running-related injuries in recreational runners. 6 Runners randomized to the foot-core strengthening group had 2.4-fold lower rate of running-related injuries within one-year study period than runners in the control group. Nevertheless, there are still many unexplored areas in the field of sport injury prevention.…”
Section: Neuromuscular Training and Sport Injury Prevention In Different Types Of Sports-what We Know And What We Do Not Know?mentioning
confidence: 88%
“…NMT and other sport injury prevention strategies can reduce the number of injuries, but only if they are properly used by athletes. Another recently published RCT revealed that a novel foot‐core muscle strengthening program was effective in prevention of running‐related injuries in recreational runners 6 . Runners randomized to the foot‐core strengthening group had 2.4‐fold lower rate of running‐related injuries within one‐year study period than runners in the control group.…”
mentioning
confidence: 99%
“…Such studies have not been conducted in youth runners, so the effectiveness of these programs remains unknown. Among adult runners, prevention programs emphasizing general lower extremity strength training have not reduced injury incidence (Toresdahl et al, 2020), though a program focused on foot muscle strengthening led to a 2.4-fold lower injury rate (Taddei et al, 2020).…”
Section: Musclementioning
confidence: 99%